European Guidelines on Perinatal Care - Oxytocin for induction and augmentation of labor. (12th December 2022) - ,; Nunes, Inês; Dupont, Corinne; Timonen, Susanna; ,; Ayres de Campos, Diogo; Cole, Vanessa; Schwarz, Christiane; Kwee, Anneke; Yli, Branka; Vayssiere, Christophe; Roth, Georges-Emmanuel; et al.
SUMMARY OF RECOMMENDATIONS: 1. Oxytocin for induction or augmentation of labor should not be started when there is a previous scar on the body of the uterus (such as previous classical cesarean section, uterine perforation or myomectomy when uterine cavity is reached) or in any other condition where labor or vaginal delivery are contraindicated. (Moderate quality evidence +++- ; Strong recommendation ). 2. Oxytocin should not be started before at least 1 h has elapsed since amniotomy, 6 h since the use of dinoprostone (30 min if vaginal insert) and 4 h since the use of misoprostol (Low quality evidence ++- -; Moderate recommendation) . 3. Cardiotocography (CTG) should be performed and a normal pattern without tachysystole should be documented for at least 30 min before oxytocin is used. Continuous CTG, with adequate monitoring of both fetal heart rate and uterine contractions, should be maintained for as long as oxytocin is used, and thereafter until delivery (Low ++- - to moderate +++- quality evidence; Strong recommendation ). 4. For labor induction, at least 1-h should be allowed after amniotomy before oxytocin infusion is started, to evaluate whether adequate uterine contractility has meanwhile ensued. For augmentation of labor, if the membranes are intact and there are conditions for a safe amniotomy, the latter should be considered before oxytocin is started (Very low quality evidence +- –; Weak recommendation) . 5. Oxytocin should be administered intravenously using the following regimen: 5 IU oxytocin diluted in 500 mL of 0.9% normal saline (NaCl) (each mL contains 10 mIU of oxytocin), in an infusion pump at increasing rates, as shown in Table 1, until a frequency of 3-4 contractions per 10 min is reached, a non-reassuring CTG pattern ensues, or maximum rates are reached (Low quality evidence ++ - -; Strong recommendation ). If the frequency of contractions exceeds 5 in 10 min, the infusion rate should be reduced, even if a normal CTG pattern is present. With a non-reassuring CTG pattern, urgent clinical assessment by an obstetrician is indicated, and strong consideration should be given to reducing or stopping the oxytocin infusion. The minimal effective dose of oxytocin should always be used. (Low ++- - to Moderate +++- - quality evidence; Strong recommendation) . 6. Use of oxytocin for induction and augmentation of labor should be regularly audited (Low quality evidence ++–; Strong recommendation ).